2020
DOI: 10.1177/1073858420960443
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Effect on the Immune System and Mitochondrial Dynamics in Diabetes, Obesity, and Dementia

Abstract: The coronavirus disease 2019 (COVID-19) is a pandemic disease, originated in Wuhan City, China. It is caused by severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) and its biology is still poorly understood. Currently, there are no vaccines and drugs/or agents that can reduce severity of this new disease. Recent data suggest that patients with age-related comorbidities, including cardiovascular disease, diabetes, obesity, hypertension, chronic kidney disease, and dementia are highly susceptible to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 36 publications
1
53
0
1
Order By: Relevance
“…[6][7][8][9][10][11][12] At present, there is no specific drug or vaccine available for SARS-CoV-2 infection. 13 The researchers worldwide face daunting challenges of developing safe and effective vaccines and medicines for COVID-19. Over 190 vaccines are currently being tested for COVID-19, out of which 42 are being tested on humans in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] At present, there is no specific drug or vaccine available for SARS-CoV-2 infection. 13 The researchers worldwide face daunting challenges of developing safe and effective vaccines and medicines for COVID-19. Over 190 vaccines are currently being tested for COVID-19, out of which 42 are being tested on humans in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…In another retrospective study on COVID-19 patients admitted to ASST Papa Giovanni XXIII, Bergamo, Italy, further confirmed that neurological manifestations are common observations seen with SARS-CoV-2 infection. Out of 1760 COVID-19 patients in this study, 137 displayed neurological manifestations that ranged from cerebrovascular issues to peripheral and central nervous system problems ( Rifino et al, 2020 ). In most patients, the neurological manifestations were observed after the resolution of COVID-19 symptoms ( Rifino et al, 2020 ), suggesting that some COVID-19 patients are likely to develop neurological issues in the long run.…”
Section: Neurological Manifestations In Coronavirus Disease 2019mentioning
confidence: 99%
“…Stroke was also observed in a significant number of COVID-19 patients in Wuhan China ( Mao et al, 2020 ). A study conducted on COVID-19 patients in Bergamo, Italy, showed that out of 137 patients with neurological symptoms, 38.7% developed cerebrovascular diseases that include ischemic/hemorrhagic strokes, transient ischemic attacks, and cerebral venous thrombosis ( Rifino et al, 2020 ). As with the other neurological manifestations, these cerebrovascular diseases displayed after the COVID-19 symptoms were resolved in most patients ( Rifino et al, 2020 ).…”
Section: Cerebrovascular Complications and Stroke In Coronavirus Disementioning
confidence: 99%
See 2 more Smart Citations